Asset Forfeiture of Corruption Proceeds Using the Non-Conviction Based Asset Forfeiture Method: A Review of Human Rights - Wulandari; Wasis Suprayitno; Kukuh Dwi Kurniawan; Merve Özkan Borsa (Universitas Muhammadiyah Malang, 2023)
Abstract One of the state's efforts to eradicate corruption is to draw up a Bill on Asset Write-off, in which there is the regulation regarding the concept of Non-Criminal-Based Asset Write-off, which this concept can be called